CACAT BUNYI KELAS KATA NOMINA PADA PENDERITA DISARTRIA : STUDI KASUS PADA ANAK USIA SEKOLAH DASAR DI UNIT TERAPI WICARA RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO DITKESAD: Sound defects, noun word level, and dysarthria patient. (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
The aim of the research is to determine sound defects of noun word level to dysarthria patient. This research was conducted at the speech theraphy unit of the International Army Gatot Soebroto Central Hospital. The technique used to analyze the data is the qualitative technique with case study approach. Case studies in this research is a single case of elementary school of the student. The results of this study are of 87 noun words that are pronounced are 283 sound defects, which consists of 46 errors substitution sound, 234 errors removal sound, and 3 errors addition sound, and there are 7 tipology of sound defects is pronounced by dysarthria patient. The recomendtions of this research can be hoped this study can help parents, families, theachers, and elementary school education institutionswho have children, a family, or atudents with speech disorders (dysarthria) in order to understand and act appropriately.